2022
DOI: 10.3389/fonc.2022.824799
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial Chemoembolization Combined With Tyrosine Kinase Inhibitors for Intermediate‐Stage Hepatocellular Carcinoma, What Else Can We Do?

Abstract: Transarterial chemoembolization (TACE) has been considered the standard treatment for intermediate-stage hepatocellular carcinoma (HCC). However, intermediate‐stage HCC is highly heterogeneous with a broad population with varying tumour burdens, liver function. This suggests that TACE monotherapy treatment might not be suitable for all patients with intermediate‐stage HCC. The administration of tyrosine kinase inhibitors (TKIs) has become an important treatment option for improving the prognosis of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…According to the 2022 BCLC version stratifications, TACE is suitable for HCC with well-defined nodules, preserved portal flow, and selective access. Systemic therapy is suitable for the BCLC stage B HCC that are diffuse and infiltrative, with extensive liver involvement, but there was no clear dividing line between the two ( 1 , 21 ). HCC in an advanced-stage (BCLC stage C) with vascular invasion or extrahepatic spread, ECOG PS ≤ 2, and preserved liver function should be evaluated for systemic therapy ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the 2022 BCLC version stratifications, TACE is suitable for HCC with well-defined nodules, preserved portal flow, and selective access. Systemic therapy is suitable for the BCLC stage B HCC that are diffuse and infiltrative, with extensive liver involvement, but there was no clear dividing line between the two ( 1 , 21 ). HCC in an advanced-stage (BCLC stage C) with vascular invasion or extrahepatic spread, ECOG PS ≤ 2, and preserved liver function should be evaluated for systemic therapy ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…SOR+TACE could be considered as an alternative therapy in cases of serious adverse events during the administration of LEN+TACE combination therapy. Furthermore, another review [6] published in 2023 explored the effectiveness and safety of TACE combined with tyrosine kinase inhibitors in the treatment of HCC with portal vein tumor thrombus, including a total of seven studies, one of which was an RCT. Additionally, there were three other network meta-analyses [38][39][40] that examined the effectiveness and safety of TACE or other drugs in the treatment of HCC, with varying numbers of studies included in each analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Transarterial chemoembolization (TACE) and tyrosine kinase inhibitors (TKIs) have emerged as critical components of treatment strategies for HCC [6]. TACE is a locoregional therapy that involves the infusion of chemotherapeutic agents directly into the hepatic artery supplying the tumor, followed by embolization.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular targeted drugs can target and inhibit these cytokine receptors, which can compensate for the lack after TACE treatment in a mechanistic manner, thereby improving the effect of TACE treatment. TACE combined with molecular targeted drug therapy has been very explored in the treatment of HCC, and there are also a large number of literatures reporting that combination therapy can effectively improve the deficiencies of TACE [46]. Masatoshi Kudo study reported [47] that TACE plus sorafenib significantly improved PFS over TACE alone in patients with unresectable HCC.…”
Section: Discussionmentioning
confidence: 99%